The influence of candidate quality, campaign issues, relationship with the media, and regional bond on voting behavior in the 2005 governor election of West Sumatra Indonesia - Adnan, Muhammad Fachri; Mohamed, Ahmad Martadha (2010)
The purpose of this research is to examine the extent to which candidate quality, campaign issues, relationship with the mass media, and regional bond influence the voting behavior in the 2005 governor election of West Sumatra Indonesia.This study was only conducted in the area Padang.Sample is determined by using multistage random sampling. Questionnaires are collected and analyzed using multinomiol logistic regression technique.The findings of this research reveal that candidate qualify and campaign issues significantly influence the voting behavior in the Governor election.On the other hand, relationship with the mass media and regional bond apparently do not seem to affect voting behavior.